Pemikiran Ekonomi Islam Pada Era Muhammad Baqir Al Sadr (1935-1980) - Jaya, Rama Indra; Arif, Muhammad (Universitas Labuhanbatu, 2024)
In the mid-20th century, significant social and political dynamics in the Arab world, particularly in Iraq, brought forth Muhammad Baqir Al Sadr, an influential Islamic intellectual and activist. Al Sadr was born in 1935, living during Iraq's transitional period from monarchy to political upheaval, creating space for new ideologies, especially in the economic realm, which was pivotal for a nation's progress. As an Islamic scholar and thinker, Al Sadr was not only involved in ideological development but also actively engaged in the evolving political dynamics in Iraq. This socio-political context laid the groundwork for the development of Islamic economic thought he championed. This paper examines how Al Sadr's socio-political background influenced his Islamic economic thought, aiming to uncover the relevance and significant contribution of Al Sadr in the development of Islamic economics at that time and its impact on contemporary Islamic economic thought. The research methodology employed is qualitative, focusing on an in-depth understanding of the background, socio-political context, and Islamic economic thought espoused by Muhammad Baqir Al Sadr. The analytical-descriptive method is also used to analyze and elucidate the application of Islamic economic concepts within the social and political context of that era. The research findings indicate that Al Sadr's economic ideas are relevant to contemporary economic issues, especially ethical values, wealth distribution, and the role of the state in achieving economic justice. However, their implementation faces challenges, such as adaptation to differing global systems and limitations in Islamic financial infrastructure. Addressing these hurdles requires a focus on changing societal behavior and understanding, supportive legal regulations, and technological integration. Despite the obstacles, a holistic approach and gradual steps are envisioned to aid in implementing Islamic economic principles..